Exploring Family Planning and Teenage Pregnancy in Malaysian: A Review of Current Knowledge and Challenges - Shalinawati Ramli; Siti Nurul Diyana Rosli (Japan University of Health Sciences & Japan International Caltural Exchange Foundation, 2025)
Index by WOS/SCOPUS/ERA (Tier 2)